AtNUDT7, a Negative Regulator of Basal Immunity in Arabidopsis, Modulates Two Distinct Defense Response Pathways and Is Involved in Maintaining Redox Homeostasis - Ge, Xiaochun (American Society of Plant Biologists, 2007)
Plants have evolved complicated regulatory systems to control immune responses. Both positive and negative signaling pathways interplay to coordinate development of a resistance response with the appropriate amplitude and duration. AtNUDT7, a Nudix domain-containing protein in Arabidopsis (Arabidopsis thaliana) that hydrolyzes nucleotide derivatives, was found to be a negative regulator of the basal defense response, and its loss-of-function mutation results in enhanced resistance to infection by Pseudomonas syringae. The nudt7 mutation does not cause a strong constitutive disease resistance phenotype, but it leads to a heightened defense response, including accelerated activation of defense-related genes that can be triggered by pathogenic and nonpathogenic microorganisms. The nudt7 mutation enhances two distinct defense response pathways: one independent of and the other dependent on NPR1 and salicylic acid accumulation. In vitro enzymatic assays revealed that ADP-ribose and NADH are preferred substrates of NUDT7, and the hydrolysis activity of NUDT7 is essential for its biological function and is sensitive to inhibition by Ca(2+). Further analyses indicate that ADP-ribose is not likely the physiological substrate of NUDT7. However, the nudt7 mutation leads to perturbation of cellular redox homeostasis and a higher level of NADH in pathogen-challenged leaves. The study suggests that the alteration in cellular antioxidant status caused by the nudt7 mutation primes the cells for the amplified defense response and NUDT7 functions to modulate the defense response to prevent excessive stimulation.